Standardization of a methodology for identification and annotation of associations between single nucleotide polymorphisms and highly polygenic traits in ruminants (2019)
Given the importance of the production of ruminants, it is necessary to investigate the genetic variants associated with the traits of economic interest in these animals, as well as the biology underlying the genotype-phenotype associations. To conduct these associations, a widely used strategy is to perform genome-wide association studies (GWAS). The GWAS must have the support of adequate quality control (QC), to then identify the associations between genetic markers type SNP and phenotypes. Additionally, the biological contextualization of these associations starts from the annotation of the genes close to the associated markers. Currently, there are several tools, including R libraries, to perform these analyses. However, it is necessary to develop a tool that allows unifying the three main steps (QC, GWAS, and annotation) for species other than human. For the above, the present work developed a methodology that unified the three mentioned steps in the R environment. The generated code was submitted for publication and is freely available in the repository https://github.com/bojusemo/Diploid-GWAS. The code was tested in two populations of ruminants, the Colombian Creole Hair Sheep and Simmental cattle. In these populations, the SNPs with low quality were removed, there was no detected population stratification, and no samples were removed for low quality. The SNP OAR26_10469468.1 was associated with the meat tenderness of Colombian Creole hair sheep. This SNP is in the gene TENM3. TENM3 protein has two domains with functions associated with meat tenderness in cattle and pigs. The SNP BovineHD4100012055 was associated with birth weight in Simmental. The closest gene to this SNP is the olfactory receptor 52E8-like, which is a member of the protein family G protein-coupled receptor (GPCR). GPCR has associated with birth weight in humans. Six markers were associated with 305-day milk yield in Simmental. Neither the closest genes of these markers nor their protein domains have been reported as associated with milk production.